Benchmarking the prevalence of care problems in UK care homes using the LPZ-i: a feasibility study - Darby, Janet; Horne, Jane; Lewin, John; Crocker, Cheryl; Coates, Emma; McEwan, Karen; Schols, Jos; Halfens, Ruud; Lohrmann, Christa; Eglseer, Doris; Gladman, John R.F.; Gordon, Adam L. (University of Nottingham, 2017)
Background: UK care homes have no mechanism for counting, collating or analyzing prevalence of care problems to benchmark quality of care. This study investigated the feasibility of the International Prevalence Measurement of Quality of Care (LPZ-i) for benchmarking in UK care homes and described facilitators and challenges to implementation.